Innate lymphoid cells: a new key player in atopic dermatitis - Jia, Haiping; Wan, Huiying; Zhang, Dingding (Frontiers in Immunology, 2023)
Atopic dermatitis (AD) is a common allergic inflammatory skin condition mainly caused by gene variants, immune disorders, and environmental risk factors. The T helper (Th) 2 immune response mediated by interleukin (IL)-4/13 is generally believed to be central in the pathogenesis of AD. It has been shown that innate lymphoid cells (ILCs) play a major effector cell role in the immune response in tissue homeostasis and inflammation and fascinating details about the interaction between innate and adaptive immunity. Changes in ILCs may contribute to the onset and progression of AD, and ILC2s especially have gained much attention. However, the role of ILCs in AD still needs to be further elucidated. This review summarizes the role of ILCs in skin homeostasis and highlights the signaling pathways in which ILCs may be involved in AD, thus providing valuable insights into the behavior of ILCs in skin homeostasis and inflammation, as well as new approaches to treating AD.